Analisis Harga Komoditas Cabai Rawit di Kabupaten Jember - Firmania, Nofi; Purwandhini, Ari Septianingtyas (Program Studi Agribisnis, 2022)
One of the agricultural commodities in Indonesia which is a potential commodity is the rice plant commodity. The purpose of this study was to determine how much the cost, revenue, income of the field rice farming and how much the efficiency of the cost of the farm rice farming and what factors influence farmers' interest in upland rice cultivation in Ranuyoso Village, Ranuyoso District, Lumajang Regency. The basic method of this research is using purposive sample method. data collection by interview, direct observation and documentation. The analysis used is revenue analysis which includes cost and revenue analysis and multiple linear regression analysis t-test, F-test (ANOVA) and R-test using the SPSS version 16 computer program. shown are the factors that influence the cultivation of upland rice in Ranuyoso Village, Ranuyoso District, Lumajang Regency are the factors of capital and income factors, while the factors that do not affect are the factors of land area and fertilizer prices.